Strains of Escherichia coli O157:H8 from human diarrhoea belong to attaching and effacing class of E coli. Issue 12 (December 1992) - Scotland, S M; Willshaw, G A; Cheasty, T; Rowe, B
Abstract : AIMS: To determine whether 17 Escherichia coli O157:H8 strains isolated from patients with diarrhoea in the United Kingdom were putative pathogens. METHODS: The strains had been isolated by the use of O157 antiserum, available for the detection of Vero cytotoxin (VT) producing strains of E coli O157 that are usually of flagellar (H) type 7, but may also be non-motile. The strains were examined for VT production, for their ability to adhere to HEp-2 cells, and for hybridisation with several DNA probes that recognise pathogenic properties of E coli. Their ability to ferment sorbitol and to produce beta-glucuronidase was also investigated, as these tests are used to discriminate VT positive O157 strains. RESULTS: The O157:H8 strains did not produce VT. All gave localised attachment to HEp-2 cells, associated with a positive fluorescence-actin staining test, and all hybridised with the E coli attaching and effacing (eae) probe. In addition to the difference in VT production, O157:H8 strains could be distinguished from VT positive O157 strains by their beta-glucuronidase activity, their failure to produce enterohaemolysin, and their lack of hybridisation with the CVD419 probe derived from a plasmid in an O157:H7 strain. CONCLUSIONS: The 0157:H8 strains had in vitro properties characteristic of the class of E coli that causes attaching and effacing lesions in epithelial intestinal cells. They may therefore be considered a putative cause of diarrhoea but their prevalence remains to be established. Several O157:H8 strains failed to ferment sorbitol in agar plates and therefore could be misidentified as VT positive O157 strains. Confirmatory tests for VT production are needed when O157 strains are isolated from faeces.